1995
DOI: 10.1128/jcm.33.8.1984-1988.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cleaving agents other than trypsin in direct agglutination test for further improving diagnosis of visceral leishmaniasis

Abstract: Trypsin treatment of Leishmania promastigote antigen has proved to be indispensible in the direct agglutination test (DAT) for the diagnosis of visceral leishmaniasis (VL) and canine visceral leishmaniasis (CVL). In the present study four antigen batches were prepared with pronase (400 g/ml), lipase (0.45% [wt/vol]), pancreatin (0.3% [wt/vol]), or 2-mercaptoethanol (2-ME) (1.2% [vol/vol]) at a ratio of 20:1 versus promastigote packed cell volume or a density of 10 8 /ml. Batches prepared in this way performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…The use of a single L. donovani isolate (1‐s) for production of the freeze‐dried antigen constitutes a major limitation for applicability in VL endemic areas where L. infantum and L. chagasi are involved. Previous studies have shown that sensitivity for VL diagnosis can significantly be increased in DAT by incorporating the indigenous or homologous L. donovani subspecies (Harith et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a single L. donovani isolate (1‐s) for production of the freeze‐dried antigen constitutes a major limitation for applicability in VL endemic areas where L. infantum and L. chagasi are involved. Previous studies have shown that sensitivity for VL diagnosis can significantly be increased in DAT by incorporating the indigenous or homologous L. donovani subspecies (Harith et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Promastigotes were harvested 7 days post‐inoculation of the basic LIT mass culture. Antigen processing was according to the improved procedures described by Harith et al. (1995).…”
Section: Direct Agglutination Test Antigen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-reactions with other pathogens may also occur . Several improvements in antigen quality and delivery have been made (Harith et al 1995;Meredith et al 1995). Although the DAT was adapted for ®eld use (Meredith et al 1995;Zijlstra et al 1997), there is a need for a simple, rapid and accurate test with good sensitivity and speci®city that can be used in the ®eld and for which no speci®c expertise is required.…”
Section: Introductionmentioning
confidence: 99%
“…18 Interestingly, β-ME treatment of promastigotes increases concanavalin A (ConA)-binding sites and also increases the sensitivity of the DAT. 19 Based on these observations, we hypothesized that carbohydrates are likely to be part of the DAT Ag.…”
Section: Introductionmentioning
confidence: 99%